Seabed Habitat Determines Fish and Macroinvertebrate Community Associations in a Subarctic Marine Coastal Nursery. Issue 6 (8th August 2017) - Dalley, Kate L.; Gregory, Robert S.; Morris, Corey J.; Cote, David
Abstract: Fish exhibit habitat‐specific distributions in heterogeneous landscapes. Many sampling techniques are limited to specific seabed types and have limited utility in comparisons of fish abundance among multiple habitats. We measured the relative abundance and the composition of fish communities in four naturally occurring coastal marine seabed types (sand–pebble, cobble, bedrock, and eelgrass) and one anthropogenic habitat type (wharf) in Newman Sound, Newfoundland, Canada, by using baited video cameras. Fish and macroinvertebrate communities were significantly different among habitat types. Winter Flounder Pseudopleuronectes americanus, Atlantic Cod Gadus morhua, and Shorthorn Sculpin Myoxocephalus scorpius were significantly more abundant over sand–pebble substrate compared with bedrock and wharf sites. Cunners Tautogolabrus adspersus and Greenland Cod Gadus macrocephalus ogac were most abundant at wharf sites. Atlantic rock crabs Cancer irroratus and American lobsters Homarus americanus avoided sand–pebble seabeds, and American lobsters were almost exclusive to bedrock sites. Cunners, Winter Flounder, and Atlantic Cod were more abundant in summer, whereas Greenland Cod and Atlantic rock crabs were more abundant during autumn months. In paired comparisons of eelgrass habitats, the community sampled by two methods was different. Relative abundance estimates from baited video cameras matched beach seine estimates for abundant predatory species (e.g., Cunner, Greenland Cod, and Atlantic rock crab), but other species, including age‐0 Greenland Cod, Shorthorn Sculpin, and White Hake Urophycis tenuis, were better represented in beach seine samples. We demonstrated substrate preferences by common coastal marine fish and crab species, which have proven difficult to enumerate via active sampling techniques in the past. Our findings will facilitate comparative studies for these species among habitat components. For species that are well sampled by using baited video cameras, this technique will advance our ability to plan for their management in the nearshore.